PSYCHOLOGICAL REHABILITATION OF PARTICIPANTS IN COMBAT ACTIONS - Gulbs, O.; Kobets, A. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The article considers the issues of theoretical analysis of psychological rehabilitation of combatants in Ukraine and abroad. The aim of the study was a theoretical analysis of the psychological rehabilitation of participants in the war dialects of Ukrmo. During the study, we used theoretical methods, including analysis, synthesis, comparison. According to the Ministry of Veterans Affairs of Ukraine, servicemen must undergo free medical and psychological rehabilitation in appropriate centers. After all, servicemen are at increased risk of developing post-traumatic stress, according to scientists, one emotionally debilitating case may be enough to develop post-traumatic stress disorder, but combat often contributes to long-term and multiple effects of traumatic events. Psychological rehabilitation involves the provision of the following services: psychological diagnosis, psychological education and information, psychological counseling, psychological support and support, psychotherapy, group work, decompression. The main areas of psychological assistance to combatants include: determining the syndrome of socio-psychological maladaptation, psychological counseling, psycho-correctional work, the formation of self-regulation skills, socio-psychological training, defining life prospects, future plans and goals. Psychological rehabilitation of combatants in Ukraine is systemic and comprehensive. The experience of the United States and Israel shows the importance of constant monitoring and, if necessary, the need for psychogenic involvement of psychologists in working with the military. Following the example of the United States, psychologists have used cognitive-behavioral therapy, acceptance and attachment therapy (ACT), and interpersonal therapy (IPT) to reduce the negative effects.
Keywords: combatants; Post-traumatic stress disorder; psychological rehabilitation; directions of psychological assistance; world experience